If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3y = -24 Solving 8x + -3y = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 8x + -3y + 3y = -24 + 3y Combine like terms: -3y + 3y = 0 8x + 0 = -24 + 3y 8x = -24 + 3y Divide each side by '8'. x = -3 + 0.375y Simplifying x = -3 + 0.375y
| x-4+99=8 | | 4-7x=3x+1 | | 3x+47=7x+10 | | 12x-24-8x=-6x+16 | | 5x+13-4x=7+4x-6 | | 3x+14=85-8x | | 1/4=z+7/4 | | 14x+120+10x=360 | | 3[6x-4]=-52 | | 4+7(-12+x)=-38 | | 24+14x=x | | 3y+z=am | | [6x-4]=-52 | | 4x-10=6x+12 | | 14x+24=x | | 6x-4=-52 | | 6x-7=5x+6 | | 8x-1=8x-x | | 6x+8x=x | | -9=x+12 | | 3x+5x-15=37 | | 7x+1=7x-x | | a(b-c)=d | | x+108=100 | | 8+4d=36 | | 18+108=126 | | 8+4d=37 | | z=6*3.14xy | | 2-11x=122+x | | 20+3n=-4 | | -9x-4=23 | | 13-7x=58-28x |